2019
DOI: 10.19044/esj.2019.v15n10p147
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Online Vegetables/Fruits Repurchase Intention: Stimulus-Organism-Response Model and Theory of Planned Behaviour

Abstract: The aim of this study is to review of concepts, theories and models related to consumer intentions. In doing this, the objective is to explore and explain the determinants of online vegetables/fruits repurchase intention based on literature review which used Stimulus-Organism-Response (SOR) Model and Theory of Planned Behaviour as basic concepts approach to put forward hypotheses for next research on consumer intention. Many research in the past examined variables as antecedents and predictors of repurchase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…From the perspective of e-commerce services, Zhang Beijia [22] takes the ease of online return policy as a stimulus variable that has a positive impact on consumers' purchase intention through the intermediary effect of perceived commodity quality, while perceived shopping risk cannot be used as an intermediary variable to influence consumers' purchase intention. From the perspective of e-commerce platform reputation and image, it is found that reputation has a positive correlation with online repurchase intention, perceived risk has a negative impact on online repurchase behavior, and subjective norms have a positive impact on consumers' purchase intention [23]. Online store image can influence consumers' online purchasing behavior through consumer interest [24], perceived value, and flow experience [25].…”
Section: Donovan and Rossitermentioning
confidence: 99%
“…From the perspective of e-commerce services, Zhang Beijia [22] takes the ease of online return policy as a stimulus variable that has a positive impact on consumers' purchase intention through the intermediary effect of perceived commodity quality, while perceived shopping risk cannot be used as an intermediary variable to influence consumers' purchase intention. From the perspective of e-commerce platform reputation and image, it is found that reputation has a positive correlation with online repurchase intention, perceived risk has a negative impact on online repurchase behavior, and subjective norms have a positive impact on consumers' purchase intention [23]. Online store image can influence consumers' online purchasing behavior through consumer interest [24], perceived value, and flow experience [25].…”
Section: Donovan and Rossitermentioning
confidence: 99%
“…Organism Response effect of perceived commodity quality, while perceived shopping risk cannot be used as an intermediary variable to influence consumers' purchase intention. From the perspective of e-commerce platform reputation and image, it is found that reputation has a positive correlation with online repurchase intention, perceived risk has a negative impact on online repurchase behavior and subjective norms have a positive impact on consumers' purchase intention [15]. Online store image can influence consumers' online purchasing behavior through consumer interest [16], perceived value and flow experience [17].…”
Section: Stimulusmentioning
confidence: 99%
“…Research of Date et al (2013) showed that attitudes, subjective norms, and perceived behavioral control influenced consumer intentions to adopt internet banking. Other studies also showed that attitudes towards behavior, subjective norms, and perceived behavioral control had a significant effect on intention (Kassem & Lee, 2004;Ma'ruf, 2005;Haghigh et al, 2012;Farizi & Tjahjono, 2016;Lestari et al, 2017;Ariyanto, 2018;Nugroho et al, 2018;Fikri et al, 2019;Setiawati et al, 2018). These studies used the Theory of Planned Behavior (TPB) as the analysis tool of the purchase intention.…”
Section: Introductionmentioning
confidence: 99%